The Trials (and Tribulations) of Complementary and Alternative Medicine in Oncology. (4th June 2019) - Ludmir, Ethan B; Jethanandani, Amit; Mainwaring, Walker; Miller, Austin B; Lin, Timothy A; Espinoza, Andres F; Verma, Vivek; VanderWalde, Noam A; Grossberg, Aaron J; Guadagnolo, B Ashleigh; Koong, Albert C; Jagsi, Reshma; et al.
Abstract: Two decades following the creation of the Office of Cancer Complementary and Alternative Medicine at the National Cancer Institute, the status of complementary and alternative medicine (CAM) research within oncology remains opaque. To better understand the landscape of CAM studies in oncology, we identified CAM-related phase III randomized controlled trials (RCTs) through ClinicalTrials.gov and compared these CAM trials to all non-CAM oncologic RCTs. Pearson χ 2 testing was used to compare proportions across groups; all tests were two-sided. Comparing the 25 identified CAM RCTs with 739 non-CAM RCTs, CAM studies were more likely to be sponsored by a cooperative group (64.0% vs 28.6%, P < .001) and less likely to be industry funded (8.0% vs 76.5%, P < .001). CAM trials disproportionately excluded disease-related outcomes as endpoints (8.0% vs 84.6%, P < .001), were unsupported by prior early-phase data (55.0% vs 96.1%, P < .001), and did not meet the primary endpoint (8.7% vs 53.0%, P < .001). Given the observed relationship between encouraging pilot data and subsequent phase III trial success, we contend that future CAM RCTs may yield more promising findings if better supported by appropriately designed and well-characterized early-phase signals.